N-Methylation of ortho-substituted aromatic amines with methanol catalyzed by 2-arylbenzo[d]oxazole NHC–Ir(iii) complexes. Issue 15 (28th March 2019) - Huang, Shuang; Hong, Xi; Cui, He-Zhen; Zhou, Quan; Lin, Yue-Jian; Hou, Xiu-Feng
Abstract : By the modification on benzo[ d ]oxazolyl-NHC-ligated cyclometalated Ir complexes, the N -methylation of ortho -substituted aromatic amines with methanol was remarkably improved. Abstract : Seven new chelated cyclometalated Ir complexes of ABO N, P, ABO N, O, and ABO N, C (carbene) based on a rigid and tunable 2-arylbenzo[ d ]oxazole backbone have been prepared for the N -methylation of amines. Among these three coordinated modes, ABO N, C (carbene) -chelated iridium-based catalysts exhibited good performance in the monomethylation of aromatic amines with methanol (MeOH) as the green methylation reagent. The steric-modified synthesis of ABO N, C (carbene) complexes was described. The most active ABO N, C (carbene) complex with marginal steric hindrance as a catalyst was obtained from the benzoxazole ring without a substituent and methyl group of the benzimidazole ring on the N-heterocyclic carbene (NHC) ligand. A variety of amines including para - and meta -substituted aromatic amines, as well as heterocyclic amines, were formulated as suitable substrates. Importantly, this catalyst considerably promoted the yield of the N -methylation of ortho -substituted aromatic amines. Controlled kinetic experiments and deuterium-labeling reactions of these ortho -substituted amines were conducted under optimized conditions. On the basis of the experimental results, a plausible mechanism was proposed.